Qualitative Protein Hydrolyzed from Nerita undata in Supralittoral Rocks and Mezolittoral Zone of Hasa Cape Using TLC - Kainama, Healthy; Sohilait, Hanoch J.; Souisa, Christian Jacob (Indonesian Journal of Chemical Research, 2021)
Gastropods are the sources of protein for coastal communities in the Maluku islands. We conducted analysis quantitative and qualitative of protein in Nerita undata meat from Hasa Cape in Saparua Island. The percentage of protein was analyzed by the Kjeldahl method. Qualitative analysis began with breaking peptide bonds in protein to amino acid components by sulphuric acid and barium hydroxide hydrolyzed. We identified amino acid compounds by using thin-layer chromatography (TLC) in butanol-acetic acid-water (8:1:1, v/v) as eluent. The result showed that N. undata meat contains 11.15% of protein and twelve amino acid compounds. There are seven essential amino acids in N. undata meat from supralittoral rocks and mezolittoral zone of Hasa cape is a source of quality protein. Thus, this species can be considered as a source of high-quality protein.